Producing Lactobacillus plantarum Dry Starter using Rice Bran Matrix - Nurhasna, Aprilia; Meryandini, Anja; Candra Sunarti , Titi (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
Background: Lactic Acid Bacteria (LAB) starter is an instant LAB culture that has been prepared to initiate lactic acid production in the fermentation process. The manufacture of BAL starter requires alternative media as a substitute for MRS media which costs a lot when used for industrial production. To protect cells, an encapsulant matrix is needed which functions to provide insulation for bacterial cells against the drying process which can damage cells and a good media is needed and is capable of being an encapsulation matrix in the manufacture of dry LAB starter. Lactobacillus plantarum NHC6 bacteria is a lactic acid bacteria that has the potential to be developed. Method: making encapsulation matrix using rice bran. The bran media consisted of 10% (w/v) rice bran added with 5% (w/v) glucose and 1% (w/v) ammonium sulfate. As much as 10% (w/v) of L. plantarum NHC6 culture which was in the late log phase was inoculated in bran media. The liquid starter was then incubated again for 14 hours at 37°C. After that, the drying process was carried out using a spray dryer at an inlet temperature of 170°C. Result: The number of live cells in the bran starter decreased after the spray drying process. Starter storage at 28°C and 4°C has a significantly different effect. Conclusion: Rice bran matrix is capable of being an encapsulating agent and is able to protect L. plantarum NHC6 cells from high temperatures during the spray drying method in the manufacture of dry starter.